Effect of Combinatory Treatment With Resveratrol and Guggulsterone on Mild Acute Pancreatitis in Mice. Issue 3 (March 2017) - Kim, Nayoung; Park, Jin Myung; Lee, Sang Hyub; Kim, Bo Hye; Son, Jun Hyuk; Ryu, Ji Kon; Kim, Yong-Tae; Lee, Woochang
Abstract : Objectives: This study was conducted to assess the preventive/therapeutic effects of combined administration of resveratrol and guggulsterone on cerulein-induced acute pancreatitis in mice. Methods: Acute pancreatitis was induced by intraperitoneal injection of cerulein in mice. Serum amylase assay and histology were performed to measure the severity of pancreatitis. Western blotting and multiplex cytokine/chemokine analysis were conducted to understand the action mechanisms of the reagents. Results: Serum amylase assay and histology revealed that the severity of acute pancreatitis was reduced by the combinatory treatment with resveratrol and guggulsterone, but the ratio of the band intensity implied that reduced nuclear factor-κB activation is primarily responsible for the effect. The reduced amounts of keratinocyte chemoattractant (chemokine [C-X-C motif] ligand 1), interferon gamma-induced protein 10 (C-X-C motif chemokine 10) and interleukin 6 expression in the sera could be involved in attenuated immune cell migration and reduced inflammation by these reagents. Conclusions: Combinatory treatment with resveratrol and guggulsterone marginally reduced cerulein-induced mild acute pancreatitis in mice.